Stellar content, planetary nebulae, and globular clusters of [KKS2000]04 (NGC 1052-DF2). Issue 4 (8th May 2019) - Ruiz-Lara, T; Trujillo, I; Beasley, M A; Falcón-Barroso, J; Vazdekis, A; Filho, M; Monelli, M; Román, J; Sánchez Almeida, J
Abstract: [KKS2000]04 (NGC 1052-DF2) has become a controversial and well-studied galaxy after the claims suggesting a lack of dark matter and the presence of an anomalously bright globular cluster (GC) system around it. A precise determination of its overall star formation history (SFH) and a better characterization of its GC or planetary nebulae (PNe) systems are crucial aspects to (i) understand its real nature, in particular placing it within the family of ultra diffuse galaxies and (ii) shed light on its possible formation, evolution, and survival in the absence of dark matter. With this purpose we expand on the knowledge of [KKS2000]04 from the analysis of OSIRIS@GTC spectroscopic data. On the one hand, we claim the possible detection of two new PNe and confirm membership of 5 GCs. On the other hand, we find that the stars shaping [KKS2000]04 are intermediate-age to old (90 per cent of its stellar mass older than 5 Gyr, average age of 8.7 ± 0.7 Gyr) and metal-poor ([M/H] ∼ −1.18 ± 0.05), in general agreement with previous results. We do not find any clear hints of significant changes in its stellar content with radius. In addition, the possibility of [KKS2000]04 being a tidal dwarf galaxy with no dark matter is highly disfavoured.